Efectos de la extracción de arena en el desarrollo del turismo sostenible en la playa la reveza del cantón palenque. - Alarcón Cevallos, Mercy Zobeida (2024)
The objective of the project focuses on analyzing the effects of sand extraction on La Reveza Beach, located in the Palenque Canton, with a particular focus on the development of sustainable tourism. Sand extraction, driven by commercial needs, presents important remains for the tourist potential of La Reveza. This unregulated process damages the ecological balance, visual quality and tourist attraction of the beach, which compromises sustainable tourism. Research is necessary to understand the effects and take measures to maintain La Reveza as a sustainable tourist attraction. The research is aligned with the United Nations sustainable development goal number 15, and the direct beneficiaries are the local community and tourists. According to the findings, sand extraction has a negative impact on tourism and the perception of sustainability in La Reveza. Furthermore, it has a significant impact on the profitability of local businesses and economic sustainability. Based on the findings, improved environmental, more sustainable extraction methods, community participation in educational programs, economic diversification, continuous observation measures, strategic partnerships and land use restrictions are proposed to reduce negative effects.